Higia Way: Aplicativo Gamificado para o Acompanhamento e Aprendizagem de Mulheres Gestantes ou Puérperas - Barreto, Luana P.; Paiva, Marina de J.; Neto, Ademar. F. Sousa; Freitas Raı́ E. T. de; Neto, F. M. Mendes; Monteiro, Bruno S. (Anais do Encontro de Computação do Oeste Potiguar ECOP/UFERSA (ISSN 2526-7574), 2023)
Women must make any health-related decisions during pregnancy. They use mobile technology to search for pregnancy-related information. Due to the specialists’ daily rush, medical appointments are increasingly brief. Pregnant women and new mothers highly value using online information to support their needs to learn more about pregnancy. With expert supervision, mHealth tools have the potential to provide pregnant women with reliable guidance, improving health outcomes for mothers and their babies. This paper presents the Higia Way, a mobile application for fast, safe, and gamified access as a learning resource for pregnant and postpartum women. Afterward, we showed data from the evaluation carried out with pregnant and postpartum women who interacted with the tool, leaving their criticisms and suggestions for improvements for future updates of the solution.